USE OF INNOVATIVE EDUCATIONAL PLAY TOOLS (APE) FROM RECYCLED MATERIALS IN LEARNING TO INCREASE THE CURIOSITY OF CHILDREN AGED 5–7 YEARS - Mado, Arifin; Salim, Agus (PT. Antis International Publisher, 2025)
Objective: This study aims to increase the curiosity of children aged 5–7 years through the use of innovative Educational Play Tools (APE) made from recycled materials. Method: The method used is Classroom Action Research (CAR) with the Kemmis & McTaggart model, which consists of the stages of planning, action, observation, and reflection. The research subjects were 15 children at KB TK Aisyiyah 25 Wage in the even semester of the 2025/2026 academic year. Data were collected through observation, interviews, and documentation, using an observation sheet on curiosity that includes indicators of asking questions, trying, exploring, and being enthusiastic. Analysis was carried out descriptively, both quantitatively and qualitatively. Results: The results showed an increase in children’s curiosity from cycle I to cycle II. In cycle I, children who reached the high category were 60% (9 out of 15 children), while in cycle II this increased to 80% (12 out of 15 children). This achievement exceeds the research success indicator, namely at least 75% of children show high curiosity. Novelty: The use of innovative APE from recycled materials has proven effective in fostering curiosity in early childhood and provides a creative learning alternative that teachers can apply in the classroom.